ANTIANXIETY ACTIVITY OF FRACTIONS AND ISOLATED COMPOUNDS OF VERBENA OFFICINALIS AERIAL PARTS (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Verbena officinalis L. (Vervain; family-Verbenaceae) has long been used in the treatment of mental disorders, but not validated systemically for traditional claims. The ethyl acetate fraction (rich in flavonoids) of V. officinalis aerial parts was subjected to bioactivity-guided fractionation to isolate main chemical constituents responsible for antianxiety activity. The column chromatography of ethyl acetate fraction yielded five fractions F1-F5, which were screened for antianxiety activity employing elevated plus maze model. F2 produced significant antianxiety activity at the dose of 16 mg/kg, p.o., upon acute administration in mice. F2 was also subjected to column chromatography, and yielded four sub fractions (F2.1 – F2.4). Upon acute oral administration of sub fractions, antianxiety activity was evaluated. Only F2.3 exhibited significant antianxiety activity, which was statistically equivalent to the standard drug (Diazepam, 2 mg/kg, p.o.). Three compounds (VO-1, VO-2 and VO-3) were isolated during the process of fractionation of bioactive fraction and sub fraction. After antianxiety evaluation of compounds, it was observed that VO-2 and VO-3 exhibit antianxiety activity.